The Influence of Relativism, Idealism, and Gender on The Students’ Academic Cheating Behaviour - Eriskawati, Evi; Januarti, Indira (Jurnal Dinamika Akuntansi, 2016)
This study aims to analyze the influence of relativism, idealism, and gender toward academic cheating behaviour of accounting students of Diponegoro University. The samples in this study were taken by using purposive samplings’ data collection method. The number of sample that used in this study was 250 respondents. The data obtained were analysed by using Linier Regression technique. The result of this research show that relativism positively significant related to academic cheating behaviour of accounting students and idealism negatively significant unrelated to academic cheating behaviour of accounting students. Moreover, gender does significantly related with negative direction of relation to academic cheating behaviour of accounting students.